2006
DOI: 10.1002/jmv.20625
|View full text |Cite
|
Sign up to set email alerts
|

Time course characteristics of human herpesvirus 6 specific cellular immune response and natural killer cell activity in patients with exanthema subitum

Abstract: The time-course of cell-mediated immunity in exanthema subitum is not well documented. The lymphoproliferative response to purified human herpesvirus 6 (HHV-6) antigen and to phytohemagglutinin was measured and natural killer (NK) cell activities determined in three consecutive specimens obtained biweekly from 18 young children and infants with exanthema subitum. Virus isolation and PCR detection of virus DNA and determination of neutralization antibody to HHV-6 and -7 were also carried out. The magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…Human herpesvirus-6 reactivation events are thought to occur periodically in healthy carriers and to be subclinical due to intact immune surveillance. Natural killer cells appear to have anti-HHV-6 function ( 6 ), as implied by their activity in the acute febrile phase of primary infection ( 7 , 8 ) and cytotoxicity against HHV-6-infected cells ( 9 ) in an interleukin-15-dependent manner ( 10 ). There is little evidence that antibody deficiency disorders increase risk of complications from infection by these viruses ( 11 ), and B cell deficiency does not increase lethality of murine roseolovirus (MRV), a betaherpesvirus related to HHV-6, in neonatal mice ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human herpesvirus-6 reactivation events are thought to occur periodically in healthy carriers and to be subclinical due to intact immune surveillance. Natural killer cells appear to have anti-HHV-6 function ( 6 ), as implied by their activity in the acute febrile phase of primary infection ( 7 , 8 ) and cytotoxicity against HHV-6-infected cells ( 9 ) in an interleukin-15-dependent manner ( 10 ). There is little evidence that antibody deficiency disorders increase risk of complications from infection by these viruses ( 11 ), and B cell deficiency does not increase lethality of murine roseolovirus (MRV), a betaherpesvirus related to HHV-6, in neonatal mice ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other herpesviruses, HHV-6-specific cell-mediated response is delayed in primary infection ( 8 ). This correlates with, and could be mechanistically related to, HHV-6 lymphotropism ( 13 15 ), since activated HHV-6-responsive T cells may be differentially susceptible to destructive viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies using peripheral blood mononuclear cells (PBMCs) have demonstrated T cell responses by both CD4 ϩ and CD8 ϩ T cells (24,40,77). However, HHV-6-specific T cell clones and T cell lines (TCLs) have been established only for CD4 ϩ T cells (40,42,69,80,81,87). The fine specificity of the T cell response to HHV-6 is largely unexplored.…”
mentioning
confidence: 99%
“…Acute HHV-6 infection stimulates cellular immunoregulatory mediators (IL-1, INF-α, INF-γ, TNF-α) and natural killer (NK) cell cytotoxicity (1,(26)(27)(28)(29). Monocyte and monocyte-derived dendritic cells are targets of HHV-6 in the pathogenesis and immunosuppressive effect during acute infection (30,31).…”
Section: Discussionmentioning
confidence: 99%